A clinical evaluation of variation in paediatric intracranial pressure waveforms - Amarah Saeed; Richard Boulton; Roddy O'Kane; Martin Shaw; Laura Moss (Brain and Spine)
Introduction: Intracranial pressure (ICP) monitoring is commonly used in investigating the aetiology of chronic paediatric neurological conditions. A series of high-amplitude spikes has been observed in overnight ICP recordings of some children, many of whom have hydrocephalus or craniosynostosis. Research question: This clinical evaluation aimed to define the spike pattern, describe the patient group in which it is most likely to occur, and conduct high-resolution waveform analysis. Material and methods: ICP waveforms from 40 patients aged 0–5 years (inclusive), recorded between 2017 and 2021 at the Royal Hospital for Children Glasgow, were retrospectively analysed. The pattern was defined through visual inspection of regions of interest by two reviewers. Patients were stratified using demographic and clinical data. R software was used to perform regression and high-resolution waveform analyses. Results: The spike pattern was defined as the presence of 2 consecutive spikes with an amplitude of at least 8 mmHg, with a gap of at least 30 min between spikes. In the adjusted Poisson regression, age was significantly associated with the number of spikes (IRR 0.8, 95% CI 0.70 to 0.92, p-value 0.001). Discussion and conclusion: Younger age was significantly associated with an increased number of spikes in this cohort. Investigation of clinical consequences of the spikes is warranted.